Breaking barriers: Elevating legume protein functionality in food products through non-thermal technologies - Yuanyuan Wei; Delu Ning; Liping Sun; Ying Gu; Yongliang Zhuang; Yangyue Ding; Xuejing Fan (Food Chemistry: X)
Legume proteins have recently gained significant interest in the food industry for their eco-friendliness and nutritional qualities. Research shows that the replacement of specific animal protein sources with legume proteins presents sustainability and economic benefit. Nonetheless, legume proteins frequently exhibit inferior functional properties and palatability compared to animal proteins. Various non-thermal technologies, including high hydrostatic pressure, ultrasound, cold plasma, pulsed electric field, and dynamic high-pressure microjet, had been investigated to enhance the functional properties of legume proteins without loss of nutritional and sensory properties. Although these technologies show potential, no systematic study has been conducted to summarize and compare their effects on different legume proteins. This review aims to fill this gap by addressing the most promising approaches of non-thermal technologies for the modification of functional properties of legume proteins. New insights are discussed, elaborating the effect of non-thermal technologies on the structural and functional behavior of proteins.